Romantic Memory Studies from the Past and Present - Nycz, Ryszard; Nycz, Ryszard; Trybus, Krzysztof (Peter Lang, 2019)
The book depicts the phenomenon of cultural memory preserved in the Polish Romantic literature, predominantly in the works of Mickiewicz, S?owacki, and Norwid (and other European poets). The primary objective is to reconstruct the cultural pattern of continuity established in Poland during the period of catastrophe. The author describes the call for a critical historiography and presents a "Slavic counterpoint" in the history of modern Europe. The key questions of the book are: Will the Romantic lesson about the transformation of history into memory and turning the past into an object of faith turn out to be a lesson about the future? The book is inspired by the German trend of contemporary reflection ? "the culture of remembrance" (Erinnerungskultur) founded on the works of the Assmanns.